Unintended acceleration : Toyota's recall crisis - Austen-Smith, David; Diermeier, Daniel; Zemel, Eitan ([London] : SAGE, 2016)
In late 2009 Toyota became the subject of media and government scrutiny after multiple deaths and injuries were attributed to accidents resulting from the unintended and uncontrolled acceleration of its cars. Despite Toyota's voluntary recall of 4.2 million vehicles for floor mats that could jam the accelerator pedal and a later recall to increase the space between the gas pedal and the floor, the company insisted there was no underlying defect and defended itself against media reports and regulatory statements that said otherwise. This case examines Toyota's reaction as the crisis escalated.
Originally Published in: Austen-Smith, D., Diermeier, D., & Zemel, E. (2012). Unintended Acceleration: Toyota's Recall Crisis. 5-311-504. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Toyota Jidosha Kabushiki Kaisha; International business enterprises -- Management -- Case studies; Organizational behavior -- Case studies; Crisis management -- Case studies